INFORMATION AND LEGAL BASES OF PREPARATION OF CITIZENS FOR MILITARY SERVICE - Volovyk, V. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2021)
The purpose of the article is to determine the essence and elements of information and legal training for military service. The article substantiates that in order to ensure a high level of development of information security and information culture of servicemen, it is necessary to form in them sufficient knowledge, skills and abilities to ensure personal and corporate information security. Attention is focused on the importance of the use of the information space by military personnel for more effective performance of their service and combat missions. The implementation of the tasks defined above is possible provided that the preparation of civilians for military service includes components of training and practicing skills necessary for the effective implementation of the information component of their future professional activities. Information activity is considered, in which a soldier participates, in a structural aspect. Three blocks of the studied phenomenon are highlighted: firstly, this is a block of information and legal knowledge, which should include the most important provisions of the legislation of Ukraine on access to public information, protection of personal data, protection of state secrets, as well as the peculiarities of working with information requests from citizens and the basics of electronic workflow. Secondly, this is an information security block, which consists of three main elements: information security of an individual, information security of the Armed Forces of Ukraine and information security of the state. Thirdly, this is a block of information hygiene, which includes the development of skills and abilities to maintain the psychological balance of a serviceman in situations of aggressive communicative influences, the ability to understand the purpose of disseminating information, to highlight false information, the purpose of which is to achieve military and non-military goals of the enemy. The article establishes that the system of information and legal training for military service should include the formation of relevant knowledge, abilities, skills and personal qualities. This can be achieved through the introduction of special courses in the system of military lyceums, as well as the introduction of a system of disciplines on the basis of higher military educational institutions and military educational subdivisions of higher educational institutions, providing for the acquisition of basic information and legal knowledge, skills and abilities. In addition, approaches to the formation of professional standards for all military registration specialties, educational and professional programs and curricula should be revised by including in them the relevant competencies in the field of information security, information hygiene and information legislation, each of which is of indisputable importance for the formation of personality. a modern serviceman as an educated, knowledgeable and information literate person who can use all the possibilities of the information space for the effective fulfillment of his service and combat missions.
Keywords: information and legal support, military service, serviceman, information hygiene, information security, information space